Incremental value of 99mTc-HYNICTOC SPECT/CT over whole-body planar scintigraphy and SPECT in patients with neuroendocrine tumours - Trogrlic, Mate; Težak, Stanko (Nuklearmedizin - NuclearMedicine, 2017)
Aim: The aim of this study was to evaluate the additional value of 99mTc-HYNIC-TOC SPECT/CT over planar whole-body (WB) scintigraphy and SPECT alone in the detection and accurate localisation of neuroendocrine tumour (NET) lesions. Methods: This study included 65 patients with a definitive histological diagnosis of NET prior to scintigraphy. Planar WB scintigraphy, SPECT, and SPECT/CT images were acquired at 4 h postadministration of 670 MBq 99mTc-HYNIC- TOC. Additional SPECT images at 10 min after tracer administration were also acquired. Clinical and imaging follow-up findings were considered as the reference standards (minimum follow-up period, 15 months). Patient and lesion-based analyses of the efficacies of the imaging modalities were performed. Results: While 38 patients exhibited metastasis of NETs, 27 presented no evidence of metastasis. Upon patient- based analysis, the sensitivity and specificity of SPECT/CT were found to be 88.9 and 79.3 %, respectively. The diagnostic accuracies of WB scintigraphy, 4h-SPECT, and SPECT/CT were 72.3, 73.8, and 84.6 %o, respectively. The area under curve (AUC) value for SPECT/CT (0.84) was the highest, followed by those for 4h-SPECT (0.75) and WB scintigraphy (0.74). The accuracy and AUC values of SPECT/CT were significantly better compared to those of WB scintigraphy (p < 0.001), 10 min-SPECT (p < 0.001), and 4 h-SPECT (p = 0.001). The findings of SPECT/CT led to the change in treatment plan of 11 patients (16.9 %o). Conclusion: The sensitivity and diagnostic accuracy of SPECT/CT in the evaluation of NET lesions outperforms planar WB imaging or SPECT alone.
Keywords: neuroendocrine tumours; receptors somatostatin; technetium 99m EDDA-HYNIC-Tyr(3)-octreotide